Functional non-synonymous variants of ABCG2 and gout risk - Stiburkova, Blanka; Pavelcova, Katerina; Zavada, Jakub; Petru, Lenka; Simek, Pavel; Cepek, Pavel; Pavlikova, Marketa; Matsuo, Hirotaka; Merriman, Tony R; Pavelka, Karel (Rheumatology (Oxford, England), 2017)
OBJECTIVES: Common dysfunctional variants of ATP binding cassette subfamily G member 2 (Junior blood group) (ABCG2), a high-capacity urate transporter gene, that result in decreased urate excretion are major causes of hyperuricemia and gout. In the present study, our objective was to determine the frequency and effect on gout of common and rare non-synonymous and other functional allelic variants in the ABCG2 gene. METHODS: The main cohort recruited from the Czech Republic consisted of 145 gout patients; 115 normouricaemic controls were used for comparison. We amplified, directly sequenced and analysed 15 ABCG2 exons. The associations between genetic variants and clinical phenotype were analysed using the t-test, Fisher's exact test and a logistic and linear regression approach. Data from a New Zealand Polynesian sample set and the UK Biobank were included for the p.V12M analysis. RESULTS: In the ABCG2 gene, 18 intronic (one dysfunctional splicing) and 11 exonic variants were detected: 9 were non-synonymous (2 common, 7 rare including 1 novel), namely p.V12M, p.Q141K, p.R147W, p.T153M, p.F373C, p.T434M, p.S476P, p.D620N and p.K360del. The p.Q141K (rs2231142) variant had a significantly higher minor allele frequency (0.23) in the gout patients compared with the European-origin population (0.09) and was significantly more common among gout patients than among normouricaemic controls (odds ratio = 3.26, P < 0.0001). Patients with non-synonymous allelic variants had an earlier onset of gout (42 vs 48 years, P = 0.0143) and a greater likelihood of a familial history of gout (41% vs 27%, odds ratio = 1.96, P = 0.053). In a meta-analysis p.V12M exerted a protective effect from gout (P < 0.0001). CONCLUSION: Genetic variants of ABCG2, common and rare, increased the risk of gout. Non-synonymous allelic variants of ABCG2 had a significant effect on earlier onset of gout and the presence of a familial gout history. ABCG2 should thus be considered a common and significant risk factor for gout.
Keywords: obyvatelé Pacifických ostrovů; Male; urate transport; lidé středního věku; New Zealand; hyperurikemie; Humans; Middle Aged; senioři; Czech Republic; Česká republika; mužské pohlaví; United Kingdom; Female; Nový Zéland; mladiství; dna (nemoc); Hyperuricemia; Gout; Aged; ABC transportér z rodiny G, člen 2; genetická variace; ABCG2; ženské pohlaví; běloši; White People; Logistic Models; Genetic Predisposition to Disease; alely; logistické modely; lineární modely; mladý dospělý; Adult; Young Adult; Pacific Island People; Spojené království; Linear Models; Neoplasm Proteins; Adolescent; ATP Binding Cassette Transporter, Subfamily G, Member 2; gout; genetická predispozice k nemoci; dospělí; lidé; nádorové proteiny; Genetic Variation; Alleles